Constraints on trenchward arc migration and back-arc magmatism in the North Patagonian Andes in the context of Nazca plate rollback - Fernández Paz, Lucía (2019)
Fil: Fernandez Paz, Lucía. Universidad de Buenos Aires, CONICET, Instituto de Estudios Andinos "Don Pablo Groeber" (IDEAN)